1998
DOI: 10.1111/j.1469-7793.1998.735bj.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxidative metabolism increases persistent sodium current in rat CA1 hippocampal neurons

Abstract: Reduced oxygen supply to the brain results in a loss of ion homeostasis and energy depletion that leads to cell death. An early effect of hypoxia in neurons is an increase in intracellular sodium concentration ([Na¤]é) which is followed by an elevation in intracellular calcium concentration ([Ca¥]é) (Friedman & Haddad, 1994a,b). In animal models of ischaemia, a low concentration of extracellular sodium ([Na¤]ï) and low concentrations of Na¤ channel blockers (which do not affect normal action potential firing) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 26 publications
5
70
0
Order By: Relevance
“…The mechanism of ischemic Na i overload is not yet fully understood. It has been speculated that the noninactivating Na ϩ current (also called sustained or persistent Na ϩ current) is responsible for Na i overload under ischemic conditions (7,11). Recent studies (24) demonstrated that the Na ϩ channel represents a target molecule for PP1.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of ischemic Na i overload is not yet fully understood. It has been speculated that the noninactivating Na ϩ current (also called sustained or persistent Na ϩ current) is responsible for Na i overload under ischemic conditions (7,11). Recent studies (24) demonstrated that the Na ϩ channel represents a target molecule for PP1.…”
Section: Discussionmentioning
confidence: 99%
“…However, a loss of membrane potential or massive Ca 2+ influx did not occur in these cells even during prolonged CN − induced chemical anoxia (Müller and Ballanyi, 2003). CN − has also been shown to increase voltage-dependent Na + currents in CA1 hippocampal cells (Hammarström and Gage, 1998).…”
Section: 14mentioning
confidence: 99%
“…It is decreased in parallel with I NaT by activation of muscarinic acetylcholine receptors and consequent phosphorylation by protein kinase C in hippocampal neurons (Cantrell et al, 1996). It is increased by hypoxia and nitric oxide in hippocampal neurons (Hammarstrom and Gage, 1998, 1999, 2000. In addition, I NaP is increased when G-protein ␤␥ subunits are coexpressed with Na v 1.2 channels .…”
Section: Introductionmentioning
confidence: 99%